PENGARUH KEPERCAYAAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI MARKETPLACE SHOPEE: Studi Kasus Pada Pengguna Marketplace Shopeee di Kota Denpasar, Bali - Anita Heptariza; Ni Komang Prasiani; Andreas James Darmawan (Universitas Triatma Mulya, 2023)
This study aims to determine 1) the effect of trust on purchasing decisions on the Shopee marketplace, 2) the effect of product quality on purchasing decisions on the Shopee marketplace, 3) the effect of trust and product quality simultaneously on purchasing decisions on the Shopee marketplace. The data collection technique used in this study was a questionnaire using a 5-point Likert scale. The analysis model is multiple regression analysis, partial test (t test statistic), and simultaneous significance test. The results showed that the value of Sig. for the effect of X1 on Y partially is 0.000 <0.05 and the value of t count is 7.503 > t table 1.998, then there is a positive and significant influence of X1 on Y. Sig. for the effect of X2 on Y partially is 0.118 <0.05 and the t value is -1.586 > t table 1.998, then there is a negative and significant effect of X2 on Y. The significance value for the simultaneous effects of X1 and X2 simultaneously on Y is 0.000 < 0.05 and the calculated F value is 215.6 > F table 3.13 so that H3 is accepted, which means that there is a positive and significant influence X1 and X2 on Y